Ecological restoration for river ecosystems: comparing the Huangpu River in Shanghai and the Hudson River in New York. Issue 7 (29th September 2015) - Wang, Xiangrong; Wang, Shixiong; Peng, Guotao; S. W. Katz, Daniel; Ling, Huanran
Abstract : Starting in the 1960s, a great deal of effort and capital was invested in an endeavor to significantly improve the quality of surface water around the United States, particularly in metropolises like New York City, New York. The Hudson River has been at the forefront of these efforts and has benefited immensely from this campaign. In parts of the developing world, such as China, similar efforts are beginning to gather the same type of momentum. Within the past decade, the Huangpu River, which flows through Shanghai into the Yangtze Estuary of China, has been a target for ecological restoration and management. It is possible to draw parallels between the cleanup efforts involved in improving the environmental conditions of the Huangpu and Hudson Rivers. Using the methodologies of series comparison (SCM), water quality index (WQI) modeling, consideration of ecological engineering, and policy strategy design, we comparatively studied the topography, functions, environmental conditions, ecological engineering countermeasures, and management policies of the two rivers to assist future forecasting of ecological restoration efforts in China.